Sensitivity and kinase activity of epidermal growth factor receptor (EGFR) exon 19 and others to EGFR‐tyrosine kinase inhibitors. Issue 5 (28th March 2013) - Furuyama, Kazuto; Harada, Taishi; Iwama, Eiji; Shiraishi, Yoshimasa; Okamura, Kyoko; Ijichi, Kayo; Fujii, Akiko; Ota, Keiichi; Wang, Shuo; Li, Heyan; Takayama, Koichi; Giaccone, Giuseppe; et al.
<x xml:space="preserve">Abstract</x> The presence of epidermal growth factor receptor (EGFR) somatic mutations in non‐small‐cell lung cancer patients is associated with response to treatment with EGFR‐tyrosine kinase inhibitors, such as gefitinib and erlotinib. More than 100 mutations in the kinase domain of EGFR have been identified. In particular there are many variations of deletion mutations in exon 19. In this study, using yellow fluorescent protein‐tagged fragments of the EGFR intracellular domain, we examined the differences in sensitivity to gefitinib, erlotinib and afatinib between several exon 19 mutants and other common EGFR mutations. We also used serum of patients undergoing treatment with EGFR‐tyrosine kinase inhibitors in this system. In addition, we examined the relative kinase activity of these mutants by measuring relative fluorescent intensity after immunofluorescence staining. We found that both sensitivity to EGFR‐tyrosine kinase inhibitors and relative kinase activity differed among several EGFR mutations found in the same region of the kinase domain. This study underscores the importance of reporting the clinical outcome of treatment in relation to different EGFR mutations.